9-cis-epoxycarotenoid dioxygenase 1 confers heat stress tolerance in rice seedling plants - Zhang, Yijin; Liu, Xiong; Su, Rui; Xiao, Yunhua; Deng, Huabing; Lu, Xuedan; Wang, Feng; Chen, Guihua; Tang, Wenbang; Zhang, Guilian (Frontiers in Plant Science, 2022)
High temperature is one of the main constraints affecting plant growth and development. It has been reported that abscisic acid (ABA) synthesis gene 9-cis-epoxycarotenoid dioxygenase (NCED) positively regulates plant resistance to salt, cold, and drought stresses. However, little is known about the function of the NCED gene in heat tolerance of rice. Here, we found that OsNCED1 was a heat stress inducible gene. Rice seedlings overexpressing OsNCED1 showed enhanced heat tolerance with more abundant ABA content, whereas the knockout mutant osnced1 accumulated less ABA and showed more sensitive to heat stress. Under heat stress, increased expression of OsNCED1 could reduce membrane damage and reactive oxygen species (ROS) level of plants, and elevate the activity of antioxidant enzymes. Moreover, real time-quantitative PCR (RT-qPCR) analysis showed that overexpression of OsNCED1 significantly activated the expression of genes involved in antioxidant enzymes, ABA signaling pathway, heat response, and defense. Together, our results indicate that OsNCED1 positively regulates heat tolerance of rice seedling by raising endogenous ABA contents, which leads to the improved antioxidant capacity and activated expression of heat and ABA related genes.